Determinants of green supply chain implementation in the food and beverage sector. (1st January 2013) - Frederick, Howard; Elting, Jens
Using a grounded theory approach, this paper extracts emerging concepts in the implementation of green supply chain management from case data of New Zealand food and beverage (F&B) companies. In search of factors that may lead to theory-building, the study relates case studies in fruit, juice, and dairy product companies through in-depth interviews with ranking general and line managers. We uncover the outline of a theoretical framework focusing on determinants of GSCM behaviour. These include strategic and operational planning; management structure, systems, and decision-making; management of people and company culture; and relationships with supply-chain members.